Ключові засади формування та розвивання систем інформаційного забезпечення постачальницької діяльності підприємств за умов цифровізації - Озарко, К.С.; Піх, М.З. (Вісник економічної науки України, 2024)
В роботі визначено актуальність досліджуваної проблеми стосовно ключових засад формування та розвивання систем інформаційного забезпечення постачальницької діяльності підприємств за умов цифровізації. За умов стрімкого розвитку цифрової економіки (її цифровізування) економічний розвиток підприємств все більше залежатиме не від матеріальних, а від інформаційних ресурсів. Цілі дослідження полягали у дослідженні принципових засад формування та розвивання систем інформаційного забезпечення постачальницької діяльності підприємств в умовах цифровізації. В праці на основі систематизування та доповнення існуючих методологій наведена характеристика ключових засад формування систем інформаційного забезпечення постачальницької діяльності за цифровізаційних умов. Можливості інноваційних технологій доцільно ефективно застосовувати у процесах моделювання, імітування, прогнозування стану системи інформаційного забезпечення постачальницької діяльності. В роботі формалізовано інформаційну систему постачальницької діяльності. The paper determines the relevance of the problem under study with regard to the key principles of formation and development of information support systems for the supply activities of enterprises in the context of digitalization. Given the rapid development of the digital economy (its digitalization), the economic development of enterprises will increasingly depend on information resources rather than material ones. The aims of the study were to investigate the fundamental principles of formation and development of information support systems for the supply activities of enterprises in the context of digitalization. The morphological method of research and the method of synthesis were used in the study. The basis for the effective implementation of the supply strategy is its effective information support. The importance of information and communication support for supply chain activities is becoming increasingly important in the context of digitalization of these processes and taking into account the transport component. In particular, thanks to satellite navigation systems and their use in supply and transportation, business managers can view online the movement of their own vehicles, raw materials, goods, etc., achieving savings in the supply system and supply chains. The main result of the introduction and further harmonious development of a corporate information system in the supply system is the formation of a highly effective management mechanism at an enterprise covering all business processes of supply (and not only) activities. Based on the systematization and supplementation of existing methodologies, the article describes the key principles of formation of information support systems for supply activities in the digitalization environment. The capabilities of innovative technologies should be effectively applied in the processes of modeling, simulation, forecasting the state of the information support system for supply activities. The paper formalizes the information system of supply activities. Summarizing, it is advisable to state that the information support of the supply activities of enterprises is a dynamic process. Information circulates in the supply chain management system with its help. When forming and constantly developing information support systems for the supply activities of enterprises in the context of digitalization, managers need to adhere to the key principles, while taking into account the innovative dynamism of methods, means of supply, etc.